Cathodic electrophoretic deposition and thermal properties of nano aluminum/fluoropolymer metastable intermolecular composite. Issue 4 (2nd October 2021) - He, Pengfei; Wang, Yajun; Li, Shihui; Wan, Yi
ABSTRACT: One challenge in the application of traditional metastable intermolecular composite (MIC) material is that MIC particles are not compatible with micro-electro-mechanical system (MEMS) based pyrotechnic device. The preparation of MIC film material can solve such problem. In this paper, we applied electrophoretic deposition method to prepare aluminum/polyvinylidene fluoride (Al/PVDF) and aluminum/polytetrafluoroethylene (Al/PTFE) MIC films. The morphological, structural and compositional information of the film samples were characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and energy dispersive spectrometer (EDS). The energy-release characteristics of Al/PVDF and Al/PTFE MIC films were analyzed by thermogravimetric (TG) analysis and differential scanning calorimetry (DSC). Micromorphology results show that the components of the films were evenly distributed but there were a few holes. DSC curves of both Al/PVDF and Al/PTFE films show that there was only one major exothermic peak and the exothermic temperature of Al/PTFE was 63°C higher than that of Al/PVDF. Kinetic analysis of main exothermic peaks indicates that the apparent activation energies ( E a ) calculated by Ozawa, Flynn-Wall-Ozawa and Starink methods were reliable. And E a of Al/PTFE is higher than that of Al/PVDF, implying that Al/PVDF is prone to react. The kinetics results of electrophoretic deposition for both Al/PVDF and Al/PTFE show that the parabolic relationship between deposition mass and deposition time exist in all experiments.